Transitivity In English Textbook: A Case Study of “Bahasa Inggris” Textbook for Tenth-Grade Students - Khalil, Ki Agus Fazrul; Yusra, Kamaludin; Udin, Udin; Soepriyanti, Henny (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims at describing the types of transitivity processes and the most dominant process types of transitivity occurring in reading texts in English textbook. The data were collected from the reading texts in “Bahasa Inggris” textbook for tenth-grade of senior high school students. The results of this study show there are various process types of transitivity occurred in the reading texts. There are relational process, material process, mental process, verbal process, behavioral process, and existential process. The most dominant process type of transitivity is relational process. It is frequently used in descriptive and recount texts which indicated that the texts contained a relational process because they serve to characterize and identify something. In addition, in narrative text the transitivity process that often appears is the material process. It is indicate that the clauses are concerned with a specific participant doing something or something that has happened in the clause. Therefore, the frequency of use of each process type is determined by the language used in the context.